Los esquemas latinoamericanos de integración frente al ALCA - Oropeza García, Arturo (Revista Mexicana de Política Exterior, 2022)
Ten years down the line from the formalization of the launch of initiatives to create the Free Trade Area of the Americas (FTAA), Latin America has experienced a series of economic problems, a decline in its development indicators and one of the most severe, deep-rooted structural crises in its history, leaving it bereft of a regional strategy to conduct negotiations in 2005. In addition to the free trade agreements that have been entered into, the author examines the workings of the five main integration mechanisms in Latin America: the Latin American Integration Association, the Central American Integration System, the Andean Community of Nations, the Caribbean Community and Mercosur. His conclusion is that the 32 countries in the region find themselves in a weak, fragmented position, which does nothing to improve their negotiating power with the United States in the FTAA. According to Oropeza, the future of Latin American integration in the context of the FTAA requires mutual recognition of the complementariness of the countries in the area, by focusing on regionalism as an expression of the maturity and political will so necessary for their development, given that globalization begins within their own borders and implies an historic challenge, which the region needs to be better equipped to take on.